Jenis-Jenis dan Sumber Pembiayaan Pendidikan pada SMA Negeri di Kabupaten Rejang Lebong - Sarwoedi, Sarwoedi; Riyan, Riyan; Hamengkubuwono, Hamengkubuwono; Istan, Muhammad (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to identify the types and sources of educational financing in State Senior High Schools (SMAN) in Rejang Lebong Regency. A descriptive qualitative approach was used, involving in-depth interviews, observations, and document studies at purposively selected SMANs. The findings indicate that the educational financing in SMAN 10 Rejang Lebong Regency comes from three main sources: the government through the School Operational Assistance (BOS) program and the Special Allocation Fund (DAK), the community through contributions from school committees, and third parties through partnerships with private institutions or alumni. Financing is divided into two main categories: operational and development. Operational financing includes daily school needs such as teacher salaries and utility costs, while development financing is used for long-term projects like infrastructure development and teacher training. However, the main challenges in fund management include delays in BOS fund disbursement and lack of transparency in managing community donations. This study recommends improving transparency and fostering better collaboration between the government, community, and private sector to create a more sustainable and effective financing model.